2011
DOI: 10.1007/s12253-011-9401-z
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Prognostic Significance of Survivin in Pediatric Medulloblastoma

Abstract: Medulloblastoma (MDB) is the most common malignant cerebellar tumor in children. Because of the significant rate of mortality and treatment-related morbidity, the identification of prognostic factors could lead to a more accurate selection of patients who can benefit from a less aggressive therapy and improve risk stratification. Survivin is an inhibitor of apoptosis protein (IAP), the expression of which has been associated with worse prognosis in MDB. However, both of its subcellular localizations may contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…[ 6 8 ] Survivin is expressed during the G 2 /M phase of the cell cycle, [ 29 ] and its expression has been detected in both the nuclei and cytoplasm of tumor cells. [ 15 ] In the nuclei, it is crucial to promote accurate mitosis progression. [ 30 ] In the cytoplasm, it suppresses apoptosis via the direct inhibition of caspase-associated proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 8 ] Survivin is expressed during the G 2 /M phase of the cell cycle, [ 29 ] and its expression has been detected in both the nuclei and cytoplasm of tumor cells. [ 15 ] In the nuclei, it is crucial to promote accurate mitosis progression. [ 30 ] In the cytoplasm, it suppresses apoptosis via the direct inhibition of caspase-associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies demonstrated that overexpression of survivin was associated with worse prognosis in glioma, [ 12 14 ] some researchers found no significant association between survivin and survival. [ 15 , 16 ] Due to the inconsistency, we aimed to systematically evaluate the prognostic role of survivin in patients with glioma through performing a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this, a possible limitation of our study could be the fact that the commercial polyclonal antibody used in our immunocytochemistry assay cannot distinguish survivin isoforms. Instead, this antibody has been shown adequate in assessing total survivin expression [38,39]. However, it is interesting to note that, through Western blot analysis there was significant positive correlation with the mRNA positivity of survivin standard, survivin-Ex3, survivin-2B and survivin-2a.…”
Section: Discussionmentioning
confidence: 99%
“…For XIAP, Survivin, FOXM1 and Her2 staining, IHC was performed on consecutive 3 µm sections as described previously (Faccion et al, 2011). Detailed information can be found …”
Section: Immunohistochemistry (Ihc) and Interpretation Of Datamentioning
confidence: 99%